Ecolinguistic approach to foreign language teaching on the example of English - Wiertlewska, Janina (Glottodidactica, 2011)
The paper deals with the problem of balance maintenance of natural languages in the context of foreign language teaching. A new paradigm of foreign language teaching in the following triad: native language – global language – second foreign language is proposed. Translingualism is treated as the only means of maintaining linguistic balance between natural languages viewed from an ecolinguistic perspective.